2008
DOI: 10.1074/jbc.m801303200
|View full text |Cite
|
Sign up to set email alerts
|

Kex1 Protease Is Involved in Yeast Cell Death Induced by Defective N-Glycosylation, Acetic Acid, and Chronological Aging

Abstract: N-Glycosylation in the endoplasmic reticulum is an essential protein modification and highly conserved in evolution from yeast to humans. The key step of this pathway is the transfer of the lipid-linked core oligosaccharide to the nascent polypeptide chain, catalyzed by the oligosaccharyltransferase complex. Temperature-sensitive oligosaccharyltransferase mutants of Saccharomyces cerevisiae at the restrictive temperature, such as wbp1-1, as well as wild-type cells in the presence of the N-glycosylation inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 88 publications
2
33
0
Order By: Relevance
“…Therefore, little support exists for the ability of tunicamycin to induce apoptosis in wild-type S. cerevisiae in YPD medium. Recently, this manner of cell death was shown to depend on Kex1, a Golgi-localized carboxypeptidase that is also important in the death of mutant cells lacking certain N-glycosylation factors and in the death of yeast cells in response to other stresses (26). The addition of an osmotic stabilizer to the culture medium also blocked death in these conditions, suggesting that the manner of cell death may be lysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, little support exists for the ability of tunicamycin to induce apoptosis in wild-type S. cerevisiae in YPD medium. Recently, this manner of cell death was shown to depend on Kex1, a Golgi-localized carboxypeptidase that is also important in the death of mutant cells lacking certain N-glycosylation factors and in the death of yeast cells in response to other stresses (26). The addition of an osmotic stabilizer to the culture medium also blocked death in these conditions, suggesting that the manner of cell death may be lysis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study arrived at the opposite conclusion (27), but the analysis was flawed by the failure to distinguish live apoptotic cells from dead cells, which are known to stain nonspecifically with FITC-VAD-FMK and other fluorophores, such as DHR123 (66). Very recently, the yeast metacaspase (Mca1) was shown to be unimportant for tunicamycin-induced cell death in YPD medium (26). Therefore, little support exists for the ability of tunicamycin to induce apoptosis in wild-type S. cerevisiae in YPD medium.…”
Section: Discussionmentioning
confidence: 99%
“…Tunicamycin is an inhibitor of N-glycosylation that strongly induces apoptosis in mammalian cells and in the budding yeast (Perez-Sala and Mollinedo, 1995; Hacki et al, 2000;Hauptmann et al, 2006;Hauptmann and Lehle, 2008). We have previously reported that tunicamycin efficiently inhibits protein N-glycosylation and induces ER stress in S. pombe (Jannatipour and Rokeach, 1995;Jannatipour et al, 1998;Beaulieu et al, 1999).…”
Section: Calnexin Is Involved In Er-stress-induced Apoptosismentioning
confidence: 99%
“…An increase in the calnexin levels due to ER stress may constitute a part of a branch in the mechanism of induction of apoptotic death. Tunicamycin is a potent inhibitor of N-glycosylation that is currently used as an elicitor of ER stress in the study of the apoptosis mechanisms in mammalian cells and in the budding yeast (Perez-Sala and Mollinedo, 1995; Hacki et al, 2000;Hauptmann et al, 2006;Hauptmann and Lehle, 2008). We have previously reported that tunicamycin induces ER stress in S. pombe and increases the expression of cnx1 ϩ , the gene encoding calnexin (Jannatipour and Rokeach, 1995).…”
mentioning
confidence: 99%
“…Kex1 is involved in the proteolytic processing of ␣-factor and of S. cerevisiae killer toxin (3,4,5,8,12,17). In addition, recent studies have shown that Kex1 plays a more general role in yeast (9,10). A whole-genome BLAST search revealed that the KEX1 orthologous gene is also present in the genome of the Aspergillus species; however, there are no reports on the enzymatic or functional properties of the Kex1 ortholog in the filamentous fungi.…”
mentioning
confidence: 99%